(untitled) (Bangladesh Journal of Zoology, 2023)
Fish biodiversity studies were undertaken from January 2012 to December 2012 to census commercially important fishes in the Sindphana Dam. The present paper deals with the variety and abundance of freshwater fishes in the Sindphana Dam near Shirur Kasar Dist. Beed [M.S] India. The results of the present investigation reveal the occurrence of 44 fish species belonging to 7 orders, 15 families, and 26 genera. Among the collected species order Cypriniformes was most dominant constituting 50% followed by order Siluriformes constituting 18%, order Perciformesconstituting 18 %, orders Osteoglossiformesand Synbranchiformes constituting 5% and orders Mugiliformesand Beloniformes constituting 2 %of the total fish species. Fish biodiversity indices species richness 44 in the total number of species (N0), 3.73 in Margalef’s index (R1), and 0.97 in the Menhinick index (R2). Species diversity was 0.47 in the Simpson index (), 1.16 in the Shannon-Weiner index (H’), 2.98 in abundant species (N1), and 2.80 in very abundant species (N2). Species evenness was 0.42 in (E1), 0.21 in (E2), 0.17 in (E3), 0.95 in (E4), and 0.97 in (E5). Bangladesh J. Zool. 51(2): 155-164, 2023